2016
DOI: 10.33549/physiolres.933504
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib Induces ER Stress and Cell Death in H9c2 Cells

Abstract: Tyrosine kinases inhibitors (TKi) represent a relatively novel class of anticancer drugs that target cellular pathways overexpressed in certain types of malignancies, such as chronic myeloid leukaemia (CML). Nilotinib, ponatinib and imatinib exhibit cardiotoxic and vascular effects. In this study, we focused on possible cardiotoxicity of nilotinib using H9c2 cells as a suitable cell model. We studied role of endoplasmic reticulum (ER) stress and apoptosis in nilotinib toxicity using a complex approach. Nilotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…As a second-generation Bcr-Abl inhibitor, nilotinib mediated apoptosis mainly through the accumulation of ROS and ER stress (Doherty et al, 2013). The increase of ROS and ER stress biomarkers (ATF4 and CHOP), was observed in nilotinib-treated H9c2 cells, which subsequently decreased MMP and activated caspase-3, markers of apoptosis (Lekes et al, 2016). Recently, Yang et al (2018) made further efforts to demonstrate that nilotinib induced ER stress to activate JNK and restrain Akt phosphorylation, which in turn suppressed glycogen synthase kinase-3 beta (GSK3β) phosphorylation and activated NOX4/ROS signaling, resulting in apoptosis.…”
Section: Trastuzumabmentioning
confidence: 99%
“…As a second-generation Bcr-Abl inhibitor, nilotinib mediated apoptosis mainly through the accumulation of ROS and ER stress (Doherty et al, 2013). The increase of ROS and ER stress biomarkers (ATF4 and CHOP), was observed in nilotinib-treated H9c2 cells, which subsequently decreased MMP and activated caspase-3, markers of apoptosis (Lekes et al, 2016). Recently, Yang et al (2018) made further efforts to demonstrate that nilotinib induced ER stress to activate JNK and restrain Akt phosphorylation, which in turn suppressed glycogen synthase kinase-3 beta (GSK3β) phosphorylation and activated NOX4/ROS signaling, resulting in apoptosis.…”
Section: Trastuzumabmentioning
confidence: 99%
“…Tyrosine kinases inhibitors (TKI) are a novel class of anticancer drugs targeting cellular pathways over-expressed in various types of malignancies [9]. Nilotinib, is an important second-generation tyrosine kinase inhibitor (TKI), widely used in the treatment of chronic myeloid leukaemia (CML) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine kinases inhibitors (TKI) are a novel class of anticancer drugs targeting cellular pathways over-expressed in various types of malignancies [9]. Nilotinib, is an important second-generation tyrosine kinase inhibitor (TKI), widely used in the treatment of chronic myeloid leukaemia (CML) [9]. It has been reported that nilotinib (Scheme 1) is the next generation of imatinib, as the first approved inhibitor of BCR-ABL, tyrosine kinase, determined the age of treatment of CML, and later studies determined its additional activity in targeting c-Kit and platelet-derived growth factor receptors (PDGFRs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The elemental formula of compound 3 was determined as C 38 H 47 NO 12 from an observed protonated molecular ion at m/ z 710.3169 (calcd 710.3171, [M + H] + ). The 1 H and 13 C NMR data showed the presence of signals for two sets of benzoyl units, four methoxy groups, and an N-methyl group (Table 2). Except for the above signals, 19 carbon signals remained; thus compound 3 was postulated to be a C 19diterpenoid alkaloid.…”
Section: ■ Results and Discussionmentioning
confidence: 99%